PENGARUH TRANSPARANSI, AKUNTABILITAS, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN PADA ORGANISASI PENGELOLA ZAKAT (Studi pada Kantor Baznas Provinsi Jambi) - Anjelika Denya Putri; Wiralestari Wiralestari; Fitrini Mansur (Jurnal Akuntansi Kompetif, 2026)
This study aims to analyze the influence of transparency, accountability, and utilization of information technology on the quality of financial reports in zakat management organizations, with a case study at the Jambi Province BAZNAS Office. This research is motivated by the existence of problems related to information transparency, management responsibility, and the utilization of information technology that has not been optimal. This study uses a quantitative approach with a multiple linear regression analysis method, and data obtained through questionnaires to 77 respondents are processed with the SPSS Statistics Version 26 program. The results of the study indicate that the variables of transparency, accountability, and utilization of information technology together have a significant effect on the quality of financial reports in zakat management organizations. The results of the study individually, show a positive and significant effect only on the variable of utilization of information technology, while transparency and accountability do not show a significant effect on the quality of financial reports in zakat management organizations